The bully pulpit [compact disc, unabridged] : Theodore Roosevelt, William Howard Taft, and the golden age of journalism - Goodwin, Doris Kearns (Simon & Schuster Audio, 2013)
Goodwin describes the broken friendship between Teddy Roosevelt and his chosen successor, William Howard Taft. With the help of the 'muckraking' press Roosevelt had wielded the Bully Pulpit to challenge and triumph over abusive monopolies, political bosses, and corrupting money brokers. Roosevelt led a revolution that he bequeathed to Taft only to see it compromised as Taft surrendered to money men and big business.